Clinical Aspects of Neonatal Hypoglycemia: A Mini Review - Edwards, Taygen; Harding, Jane E. (Frontiers in Pediatrics, 2021)
Introduction Neonatal hypoglycemia is common and a preventable cause of brain damage. The goal of management is to prevent or minimize brain injury. The purpose of this mini review is to summarize recent advances and current thinking around clinical aspects of transient neonatal hypoglycemia. Results The groups of babies at highest risk of hypoglycemia are well defined. However, the optimal frequency and duration of screening for hypoglycemia, as well as the threshold at which treatment would prevent brain injury, remains uncertain. Continuous interstitial glucose monitoring in a research setting provides useful information about glycemic control, including the duration, frequency and severity of hypoglycemia. However, it remains unknown whether continuous monitoring is associated with clinical benefits or harms. Oral dextrose gel is increasingly being recommended as a first-line treatment for neonatal hypoglycemia. There is some evidence that even transient and clinically undetected episodes of neonatal hypoglycemia are associated with adverse sequelae, suggesting that prophylaxis should also be considered. Mild transient hypoglycemia is not associated with neurodevelopmental impairment at preschool ages, but is associated with low visual motor and executive function, and with neurodevelopmental impairment and poor literacy and mathematics achievement in later childhood. Conclusion Our current management of neonatal hypoglycemia lacks a reliable evidence base. Randomized trials are required to assess the effects of different prophylactic and treatment strategies, but need to be adequately powered to assess outcomes at least to school age.